Studying the Synchronization for Multiple Transmitter- Receiver Nano Quantum Cascade Lasers. - Resan, Hiba; Waried , Hussein (University of Thi-Qar Journal of Science, 2024)
In this paper, the chaos synchronization of four Nano quantum cascade lasers with optoelectronic feedback was investigated. The present system consists of two receiver lasers and two transmitters lasers. The rate equation model was modulated to study the effect of the Purcell factor F and the spontaneous emission factor because of their importance in a nanocavity. The results indicated that the suggested system, realize the chaos synchronization. Also, the nanocavity parameters F and β, have significant effect on the chaos synchronization quality and may lead to lose it. Furthermore, the results showed the weak effect of delay time on the performance of lasers.